The rise of megacities : challenges, opportunities and unique characteristics - Kleer, Jerzy; Anna Nawrot, Katarzyna (World Scientific Publishing Europe Ltd, 2018)
Megacities of over 10 million inhabitants are unique entities in their own right, both challenging and supporting the policies, governance and cohesion of states.